Skiing Trauma and Safety: Sixteenth Volume 2006
DOI: 10.1520/stp39643s
|View full text |Cite
|
Sign up to set email alerts
|

On Piste Fatalities in Recreational Snow Sports in the U.S.

Abstract: This study documents fatalities and risk factors in alpine winter sports. The authors have tracked all known fatalities (n=854) occurring to recreational skiers and snowboarders within the boundaries of ski resorts in the United States since January 1978 through the winter of 2004/05. Data are limited to trauma deaths. Medical emergency deaths, deaths to employees, and deaths involving uphill lift facilities were excluded. Fatality data came from three sources: the U.S. Consumer Product Safety Commission (CPSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…The mean incidence of fatalities between 2008/09 and 2017/18 was 36.9 ± 7.9 deaths per year. In comparison, studies by Shealy et al [9] and Ruedl et al [6] reported 38.5 ± 6.0 and 41.1 ± 6.4 deaths on average per winter season. The overall incidence rate of 0.70 deaths per million skier days is lower than shown in studies by Ruedl et al [6], Shealy et al [9] and Bianchi et al [8], reporting 0.79, 0.75 and 0.70 deaths per million skier days.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The mean incidence of fatalities between 2008/09 and 2017/18 was 36.9 ± 7.9 deaths per year. In comparison, studies by Shealy et al [9] and Ruedl et al [6] reported 38.5 ± 6.0 and 41.1 ± 6.4 deaths on average per winter season. The overall incidence rate of 0.70 deaths per million skier days is lower than shown in studies by Ruedl et al [6], Shealy et al [9] and Bianchi et al [8], reporting 0.79, 0.75 and 0.70 deaths per million skier days.…”
Section: Discussionmentioning
confidence: 74%
“…Regarding traumatic and nontraumatic fatal injuries on ski slopes, a rising trend of deaths rates could be shown between the period 1980 and 2001 by Xiang and Stallones [7] and death rates ranged from 0.53 to 1.88 deaths per million skier days. Later, after the turn of the millennium, the number of traumatic deaths among skiers has remained relatively stable, with incidences ranging from 0.37 [6] to 0.70 [8] and 0.75 deaths per million skier days [9]. Due to the lack of published literature/studies, the development of nontraumatic death incidences in the last two decades cannot be described properly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that mainly male skiers older than 50, at an average altitude of 1700 m, were involved in most deaths, suggesting that gender, age, and altitude may be important risk factors for death on the ski slope. Other 2,5,6 have also shown that primarily males are involved in fatalities on ski slopes. A potential reason for the higher death rate in male skiers might be that males show, in general, higher risk-taking behavior on ski slopes, and they ski faster compared to females.…”
Section: Discussionmentioning
confidence: 98%